2022
DOI: 10.1111/lang.12557
|View full text |Cite
|
Sign up to set email alerts
|

First Language Literacy and Second Language Oracy: A Partial Replication of Foster and Skehan (1996)

Abstract: This article responds to calls for greater inclusivity in second language acquisition research and, more specifically, to calls to explore further the impact of first language literacy on second language oracy (e.g., Tarone et al., 2009). We conducted a partial replication of Foster and Skehan's (1996) influential study of task complexity, planning time, and performance over measures of complexity, accuracy, and fluency. The initial study and others had provided robust evidence to suggest that planning time ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 47 publications
(92 reference statements)
0
9
0
Order By: Relevance
“…Ryan et al. (2023) replicated a foundational study in task‐based language teaching by Foster and Skehan. Using a WEIRD sample of part‐time English language students in the United Kingdom, Foster and Skehan (1996) found that the addition of pretask planning increased the linguistic quality of speech performance, a finding that many authors have replicated since.…”
Section: Six Case Studiesmentioning
confidence: 91%
See 3 more Smart Citations
“…Ryan et al. (2023) replicated a foundational study in task‐based language teaching by Foster and Skehan. Using a WEIRD sample of part‐time English language students in the United Kingdom, Foster and Skehan (1996) found that the addition of pretask planning increased the linguistic quality of speech performance, a finding that many authors have replicated since.…”
Section: Six Case Studiesmentioning
confidence: 91%
“…The authors speculated that differences in proficiency may have been one of the important causes of the differences found. Ryan and colleagues (2023) did not reproduce the positive effect that planning time was found to have on task performance by Foster and Skehan (1996). And finally, Zinszer and colleagues (2023) did not find the hypothesized effect between statistical learning and literacy that Arciuli and Simpson (2012) observed and that Qi et al.…”
Section: Replication Reproducibility and Ethics In Nonacademic Resear...mentioning
confidence: 93%
See 2 more Smart Citations
“…An additional benefit of registered reports is that the peer review of the proposed study, which may include the author(s) of the initial study, can help researchers to conceive the most valid and reliable replication design, addressing the challenges illustrated above of deciding the methods for replicating a study (for an example from the SLA for all? initiative, see Ryan et al., 2023).…”
Section: The Challenges Of Some Key Open Research Practices and How T...mentioning
confidence: 99%